1970
DOI: 10.3181/00379727-133-34589
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of Porcine Insulin, Proinsulin, and Connecting Peptide by the Isolated Rat Liver

Abstract: After intravenous injections, we have found the immunological half-life of purified porcine proinsulin to be more prolonged than purified porcine single-component insulin in both swine (22 and 9 min, respectively) and in baboons (18 and 8 min, respectively). Studies in humans have also indicated a longer half-life of proinsulin than insulin (1). These findings have prompted the present investigation of the in vitro degradation of insulin, proinsulin, and the connecting peptide that links the A and B chains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

1974
1974
1985
1985

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 4 publications
2
40
0
1
Order By: Relevance
“…Several in vivo investigations carried out in man and dog indicate that this organ removes significant quantities of insulin (1)(2)(3)(4). This has been further substantiated in the rat by measurement of insulin removal in vitro by liver perfusion techniques (5)(6)(7)(8)(9). Such in vitro studies have suggested that the insulin removal was greater when less insulin reached the liver (10,11).…”
Section: Introductionmentioning
confidence: 87%
“…Several in vivo investigations carried out in man and dog indicate that this organ removes significant quantities of insulin (1)(2)(3)(4). This has been further substantiated in the rat by measurement of insulin removal in vitro by liver perfusion techniques (5)(6)(7)(8)(9). Such in vitro studies have suggested that the insulin removal was greater when less insulin reached the liver (10,11).…”
Section: Introductionmentioning
confidence: 87%
“…Nach Stimulation der B-Zelle durch intravenöse Verabreichung von Glucose oder Arginin erreicht das C-Peptid/InsulinVerhältnis in der Portalvene nach 90-120 Sekunden etwa den Wert l, was deutlich macht, daß beide Peptide iii äquimolaren Mengen sezerniert werden (5,6). Die Passage durch die Leber führt -in Abhängigkeit von der Konzentration (7) und offensichtlich als Ausdruck seiner Wirkung (8) -beim Insulin zu einer Extraktion von 50-70% (7,(9)(10)(11)(12)(13)(14), wogegen die hepatische Extraktion von C-Peptid nur gefing ist (l 1). Insulin wird mit einer Halbwertszeit von etwa 5 Minuten (15,16) Studien (13,17) sind neben dem Plasmapool wenigstens zwei weitere Verteilungsräume anzunehmen, ein mit dem Plasma schnell austauschendes Kompartiment, das möglicherweise durch die Organe Leber, Herz und Niere repräsentiert wird, und ein langsam austauschendes Kompartiment, das im wesentlichen den Organen Muskel, Fettgewebe und Haut entsprechen dürfte.…”
Section: Kinetik Und Konzentration Im Plasma Von Proinsulin Insulin unclassified
“…These studies have been recently reviewed (3,4). In the circulation, there appears to be negligible conversion of proinsulin to insulin (5)(6)(7)(8)(9), and proinsulin degradation in the liver appears to be independent of any conversion to insulin (10,11). However, such processes operating at the plasma membrane of target cells were specifically not excluded by these studies.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that the lower uptake of proinsulin by the liver insulin receptors, as well as its much slower degradation by the liver (10,11,14,37), allows more of the secreted proinsulin to reach the peripheral circulation and may account for the longer half-life of proinsulin (38) and its prolonged activity in vivo (3,4,39) when compared to insulin. There are several clinical states in which the proportion and/or the properties of the circulating proinsulin component(s) de-viate from the normal pattern (40).…”
Section: Steady-state Studiesmentioning
confidence: 99%